ANALISIS SEMIOTIKA ROLAND BARTHES TERHADAP REPRESENTASI MITOS KEPERCAYAAN BUDAYA JAWA TIMUR DALAM FILM SEKAWAN LIMO - Nikodemus Hendra Widiawan; Muadz Muadz (Solidaritas, 2025)
T This study analyzes the representation of myths and cultural beliefs of East Java in BayuSkak’s film Sekawan Limo using Roland Barthes’ semiotics. The film presents cultural taboos suchas climbing during the month of Suro, looking back while hiking, the requirement of even-numberedclimbers, and the prohibition of taking objects from the forest. A qualitative descriptive method wasapplied with Barthes’ three levels of meaning: denotation, connotation, and myth. The findings showthat Sekawan Limo not only entertains but also represents East Javanese local wisdom. The culturalprohibitions depicted carry messages of caution, respect for nature, and inherited spiritual beliefs.The film serves as a medium of cultural preservation and strengthens local identity throughmeaningful signs.Keywords: Roland Barthes’ semiotics, representation, myth, East Javanese culture,